Exploring the potential for achieving the triple-bottom-line of sustainability through offsite manufacturing - Sutrisna, Monty; Leong, Chris; Hammad, Ahmed; Zaman, Atiq (2018)
Triggered by the rapid depletion of natural resources, sustainability has now becoming a popular topic that has been linked to various aspects of human’s life. Given the very scale of the global construction industry, sustainability has emerged as one of the main features in the construction industry including in choosing the construction method such as offsite manufacturing (OSM) in construction. In fact, one of the main advantages of OSM has been expected as its potential to minimise waste as well as higher level of productivity and hence supporting sustainability. However, it has also been reported that despite all its advantages, the uptake of OSM is still considered relatively low in the construction industry. In discussing about sustainability, various scholars have championed the importance of looking into this matter through a more holistic view of sustainability including economical, social and environmental. This is also known as the triple bottom-line of sustainability. This paper presents a review of the current development in analysing the achievement of the triple bottom-line of sustainability throughout the lifecycle of offsite construction projects. The outcomes of this review are expected to unveil various points within the lifecycle of projects delivered with the offsite construction techniques that can be improved to better facilitate the achievement of the triple-bottom-line of sustainability in these projects. The findings can be used by practitioners to improve and better justify the implementation of offsite construction techniques and subsequently, further promoting the use of such techniques in the construction industry.